The Cortona Heritage Project: documenting, enhancing and spreading the cultural heritage - Puma, Paola; Rossi, Stefano; Nicastro, Giuseppe (Eikón / Imago, 2019)
The paper presents the ﬁrst results of the Cortona Heritage Project, which takes the opportunity to use the techniques of Virtual heritage to implementing concrete and innovative modes making the very rich cultural heritage of the ancient Tuscan city accessible for more people and engaging new publics by promoting its knowledge among young generations. The Cortona Heritage Project was founded in 2016 in collaboration between the University of Florence, the Municipality of Cortona and the Museo dell’Accademia Etrusca e della Città di Cortona-MAEC.